A new model of emulsion flow in porous media for conformance control. (1st April 2019) - Yu, Long; Ding, Boxin; Dong, Mingzhe; Jiang, Qi
Abstract: Emulsion flow in porous media is of paramount importance to the use of emulsions in the conformance control and enhanced oil recovery processes. In this paper, a new theoretical model, incorporating physical properties of porous media, physicochemical properties of the emulsion system, injection strategy, and the interactions between porous media and emulsion, was developed to quantitatively describe flow behaviors of emulsions in porous media. The resistance factor of an emulsion when transported in porous media was first derived through a-two phase flow method. The strong interaction between emulsion droplets and porous media was characterized by the capillary resistance force in the model. A non-uniform capillary model which considers size differences of the pore-body and pore-throat in porous media was proposed to represent the complicated real porous media. By analyzing the adsorption and plugging properties of different emulsion droplets in the non-uniform capillary model, the capillary resistance force was finally determined. To describe emulsion flow in the subsequent water flooding process after emulsion injection, an emulsion dilution factor was introduced into the model. A set of experimental data of emulsion flow in sandpacks was used to validate the reliability of the newly proposed model. The validation results show that by appropriately choosing coefficients, the simulated results are in good agreement with experimental values, with a maximum average absolute error less than 10%, and the developed theoretical flow model can be used to describe emulsion flow behavior in porous media.